Construction of on-line monitoring system for self provided power plants in Shandong Power Grid. Issue 4 (January 2021) - Zhu, Lingkai; Zhang, Haijing; Zheng, Wei; Wang, Qian; Wang, Weishuai; Zhang, Yanpeng; Li, Honghai; Ren, Xinghui
Abstract: Based on the analysis of the problems existing in the operation of self provided power plants in Shandong power grid, it is proposed to develop and build an on-line monitoring system for self-contained power plants, which can realize on-line monitoring of power generation and consumption operation and on-line analysis of power generation and consumption behavior characteristics, realize automatic collection of electricity data, provide scientific and quantitative monitoring means, and promote standardized operation and orderly development of self provided power plants.